Under the Nakba Tree Fragmnts of a Palestinian Faemily in Canada - Househ, Mowafa Said (Our Lives: Diary, Memoir, and Letters, 2022)
Mowafa Said Househ's family fled Palestine in 1948 and arrived in Canada in the 1970s. He spent his childhood in Edmonton, Alberta, where he grew up as a visible minority and a Muslim whose family had a deeply fractured history. In the year 2000, when Mowafa visited his family's homeland of Palestine at the beginning of the Second Intifada, he witnessed the effects of prolonged conflict and occupation. It was those observations and that experience that inspired him not only to tell his story but to realize many of the intergenerational and colonial traumas that he shares with the Indigenous people of Turtle Island. His moving memoir depicts the lives of those who live on occupied land and the struggles that define them.